The Role of Organizational Commitment in the Influence of Servant Leadership and Perceived Organizational Support on Organizational Citizenship Behavior Among Employees at the Banyumas District Health Office - Pratama, Bintang Rizki; Darmawan, Akhmad; Purnadi, Purnadi; Haryanto, Totok (International Journal of Business and Applied Economics, 2025)
This study aims to examine the influence of Servant Leadership and Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB), with Organizational Commitment as a mediator, among employees at the Banyumas District Health Office. The research employs a quantitative approach with saturated sampling, involving 110 respondents. Data were analyzed using the Structural Equation Modeling - Partial Least Squares 3.0 method to test the relationships between variables. The findings reveal that Servant Leadership, Perceived Organizational Support, and Organizational Commitment have a positive and significant effect on OCB. Additionally, Servant Leadership and POS positively and significantly influence Organizational Commitment. Furthermore, Servant Leadership and POS positively and significantly impact OCB through Organizational Commitment.